“A More Permanent Familiarity”: Value and the Paternal Image on United States Currency - Heinz Tschachler (European Journal of American Studies)
When in April 2016, the United States Department of the Treasury officially announced the redesign of the $20 bill, the plan provided that the portrait of an “exemplary American woman” would replace Andrew Jackson’s. This article explores whether such a portrait would make any substantive difference to women’s marginalization in public life. It interprets the exclusive presence of portraits of “Presidents” on the nation’s currency as tantamount to the real power of men in society and, as well, to a metaphorical understanding of the nation in family terms. Indeed, from the beginning of the republic the president has been seen at one and the same time as an older male authority figure and a privileged bearer of value. All the evidence suggests, therefore, that the appearance of a portrait of a woman on the currency is more than simply a matter of time, just as there is little evidence that a woman leading the United States is simply a matter of time.